Active starch-gelatin films for shelf-life extension of marinated salmon. (October 2017) - Moreno, Olga; Gil, Àgueda; Atarés, Lorena; Chiralt, Amparo
Abstract: Biodegradable active films were obtained by casting, using glycerol plasticized oxidized corn starch (OS) and bovine gelatine (BG) blends (1:1 mass ratio), with and without ethyl lauroyl arginate (LAE) as antimicrobial agent (1.3 g LAE/100 g polymer). Water vapour barrier capacity and colour of the films conditioned at 53 or 88% relative humidity were determined. Both LAE incorporation and high RH promoted film browning, coherently with the progression of Maillard reactions between amino groups of gelatine or LAE and carbonyl groups of oxidized starch. These compounds imparted antimicrobial properties to the films with and without LAE, both exhibiting antilisterial activity in in vitro tests. Packaging of marinated salmon samples in these films greatly reduced the total viable counts, which remained below the legal limit after 45 storage days at 5 °C. Nevertheless, films were not effective at controlling weight loss of salmon samples during the cold storage. Highlights: Oxidized starch-gelatin blend films, with and without LAE, extended marinated salmon shelf life. Oxidized starch-gelatin blending produced antimicrobial Maillard compounds (film browning). Both browning reaction and antimicrobial activity progressed during the film storage. Water barrier capacity of the films was not enough to prevent salmon water loss during storage. TVC of salmon samples packaged with the films remained below the legal limit after 45 storage days.